1985
DOI: 10.1039/p29850001279
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of excited-state xanthone and thioxanthone by inorganic anions

Abstract: The quenching rates of both singlet and triplet states of thioxanthone by a group of inorganic anions have been determined, enabling a comparison of their reactivities. The quenching rates of triplet xanthone were also measured. All determinations were made in MeCN-H,O (3: 2 v/v). The various rates are correlated with the free-energy change for electron-transfer, AG,", according to the treatments of Rehm and Weller and of Polanyi; an unexpectedly good fit is given by the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…The fluorescence quenching of organic chromophores by inorganic anions has been reported for a number of hydrocarbon and heterocyclic systems (26)(27)(28)(29)(30). In several of these studies, triplet states of the chromophores were the only products observed from singlet state quenching and provide precedence for our observations (26,30).…”
Section: Energetics and Reactive Intermediate Formationsupporting
confidence: 68%
“…The fluorescence quenching of organic chromophores by inorganic anions has been reported for a number of hydrocarbon and heterocyclic systems (26)(27)(28)(29)(30). In several of these studies, triplet states of the chromophores were the only products observed from singlet state quenching and provide precedence for our observations (26,30).…”
Section: Energetics and Reactive Intermediate Formationsupporting
confidence: 68%
“…In our polar and hydroxylic reaction medium, the lowest triplet state of xanthone has a pp* configuration with little tendency towards hydrogen abstraction; 13 however, it can be quenched by electron transfer from a suitable donor D. [14][15][16][17][18][19] In this work, we used triethylamine and DABCO (diazabicyclo[2.2.2]octane) for that purpose. The former has the advantage that the resulting radical cation D 1 and subsequent species, e.g., a-amino alkyl radicals, are practically nonabsorbing throughout the visible and near UV, but its volatility makes it more difficult to preadjust a desired concentration and to keep it constant during a series of measurements; furthermore, a variety of secondary thermal reactions, which also involve surplus xanthone molecules in their ground state, can complicate two-pulse experiments with longer interpulse delays.…”
Section: Photoinduced Intermediate Formationmentioning
confidence: 99%
“…1) comparable with the rate constants determined for 9,10-dicyanoanthracene 6 and thioxanthone. 7 The configuration of the major diastereoisomer 2a was determined by NOE-spectroscopy and by comparison of the aminoalcohol 4a which resulted from the LAH-reduction of 2a with the literature-known compound. 8 The relative configuration of the two minor components were determined from the 3 J HH coupling constants of the hydrogen proximal to the azido group.…”
mentioning
confidence: 99%